Patterns and Predictive Factors of Health-Related Quality of Life Among Community-Dwelling Patients With Hypertension: A Cross-Sectional Study From Thailand - Suthasinee Srinoon; Jeeraporn Kummabutr; Pantip Sangprasert; Siriluck Kaewsriwong; Korawan Keaittipattanachai (Journal of Holistic Nursing, 2026)
Purpose To describe the patterns of health-related quality of life (HRQoL) across four WHOQOL-BREF domains and to identify independent predictive factors—including cognitive health mindfulness—among community-dwelling adults with hypertension in an urbanized area of Thailand. Design Descriptive cross-sectional study. Methods Three hundred and thirty adults (≥35 years) with physician-confirmed hypertension were recruited by multi-stage stratified random sampling from 11 sub-district health promoting hospitals. Measures included the WHOQOL-BREF, Stress Scale (ST-5), Intellectual Well-Being Scale, and the 17-item Cognitive and Behavioral Sati Scale (CBSS). Descriptive statistics, Pearson correlation, and multiple linear regression were applied. Findings Overall HRQoL was moderate in 55.8% of participants (M = 94.53, SD = 11.35). Cognitive health mindfulness was moderate in 64.2% (M = 50.00, SD = 12.34; α = 0.884). Multiple regression identified four independent predictors: intellectual well-being (β = 0.536), stress (β = −0.175), cognitive health mindfulness (β = 0.157), and absence of complications (β = 0.108); R 2 = 0.446, F (6, 323) = 43.009, p < .001. Conclusions Cognitive health mindfulness was an independent, though modest, predictor of HRQoL among hypertensive patients, alongside intellectual well-being, stress, and absence of complications. These cross-sectional findings support incorporating mindfulness and intellectual well-being screening, alongside stress management and complication prevention, into holistic primary hypertension nursing assessment, with intervention effectiveness to be established by future longitudinal and experimental research.